State Responbility In Protecting Civil Society Human Rights - Cahyani, Hania Pramesti; Kinasih, Pramesti Ivana Putri; Arta, Danang Imam Danu; Nisah, Khamilatun; Wahyu, Azzahra Sania (Universitas Duta Bangsa Surakarta, 2023)
This research is a research that examines in a normative juridical manner the responsibility of the warring state to protect the human rights of civilians in territory of the country. This research aims to provide understanding to the public regarding the protection of human rights that must be fulfilled by the state when it becomes a party to a war. The research method used is a normative juridical research method that examines international legal documents namely the 1907 Hague Convention, the 1949 Geneva Convention and Protocol I and Protocol II 1977. combatants and civilians, if that country has decided to become a party to the war. Nonetheless, the state still has the obligation to guarantee with all its might to safeguard the safety of its country's civilians who are not directly involved in the war as a form of fulfillment of human rights as stipulated in these conventions. In addition to maintaining the safety of civilians, the state also has an obligation to prevent combatants from committing acts that can be categorized as war crimes.